FORMATION AND FUNCTIONING OF THE GRAIN MARKET UNDER NEW CHALLENGES THROUGH THE APPLICATION OF CLOUD TECHNOLOGIES IN ACCOUNTING AND ANALYTICAL SYSTEMS FOR COST ANALYSIS AND AUDIT - KORОBOVA, Nataliia; VDOVENKO, Nataliia; GOLOVNINA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The current stage of development of Ukraine’s agrarian economy is characterized by an intensification of systemic challenges caused by the transformation of global agricultural markets, the impact of martial law, disruptions in logistics chains, increased production risks, rising price volatility, and a general growth of economic uncertainty. Under these conditions, the grain market, as a core segment of the agri-food market and a key element in ensuring the country’s food and economic security, requires a rethinking of approaches to its formation and functioning, as well as the improvement of regulatory instruments in line with ongoing institutional and technological transformations. Of particular relevance is the issue of effective cost management by grain market participants, as the cost component largely determines the competitiveness of grain products, the financial sustainability of enterprises, their ability to adapt to crisis conditions, and the effectiveness of integration into global trade flows. The purpose of this article is to substantiate the theoretical and practical foundations of the formation and functioning of the grain market under new challenges through the application of cloud technologies in accounting and analytical management systems, as well as in cost analysis and audit, taking into account contemporary transformations of the agrarian sector. The article demonstrates those traditional systems of financial and managerial accounting, cost analysis, and audit in the agrarian sector are often insufficiently flexible and responsive, which complicates managerial decision-making under conditions of high market dynamics and increasing volumes of information. It is substantiated that cloud technologies form a new architecture of accounting and analytical systems by integrating primary accounting, management accounting, financial analysis, and audit procedures into a unified digital environment with real-time data access. It is determined that the use of cloud platforms enhances the transparency of costs by crops, technological operations, and responsibility centers, minimizes the risks of data loss or distortion, and improves the quality of cost planning through the use of analytical dashboards, scenario modeling, and forecasting tools. The application of the cost variance indicator is proposed as a basic instrument of accounting and analytical support for cost analysis and audit in the grain sector, enabling a quantitative assessment of the difference between actual and standard costs and serving as an indicator of the quality of managerial decisions within production and logistics chains of the grain market. It is shown that under digitalization conditions, cost auditing is transformed from retrospective control into a tool of continuous monitoring, while the automation of audit procedures reduces subjectivity and increases the reliability of financial information. The obtained results confirm that the application of cloud technologies in accounting and analytical systems for cost management, analysis, and audit is a key prerequisite for improving the efficiency of the grain market under new challenges, reducing production and logistics risks, strengthening the competitive positions of grain producers, and forming a more transparent and sustainable development model of the grain sector.
Keywords: grain market; cost audit; grain sector; costs; cost management; cost analysis; cloud technologies; accounting and analytical systems; digitalization; accounting and analytical support; wheat; maize; barley; logistics; control; global agricultural market; emerging challenges